2008
DOI: 10.2174/1874398600801010068
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Variation of Ecophysiological Responses to CO2 in Picea glauca Seedlings

Abstract: Abstract:To investigate genetic variation in the response of white spruce (Picea glauca (Moench) Voss) to CO 2 elevations, one-year-old seedlings of 11 provenances from Ontario were grown at 360, 530 and 700 mol mol . There were no significant between-provenance differences in any of the above responses; nevertheless, the ecophysiological performance of seedlings was closely correlated with the temperature and precipitation regimes of the seed origin. In addition, provenance significantly affected seedling tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
1
5
0
Order By: Relevance
“…Photosynthetic rate ( A max ) showed a clinal variation with southern populations exhibiting a higher A max than northern populations (Figure 4B ). This pattern is in agreement with previous findings (Kogami et al, 2001 ; Dang et al, 2008 ; Qiuhong et al, 2013 ; Benomar et al, 2015 ). However, the results are in conflict with others that demonstrated a positive latitudinal cline in A max driven by needle nitrogen ( N mass ) and carboxylation capacity ( V c max ) (Oleksyn et al, 1998 ; Soolanayakanahally et al, 2009 ).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Photosynthetic rate ( A max ) showed a clinal variation with southern populations exhibiting a higher A max than northern populations (Figure 4B ). This pattern is in agreement with previous findings (Kogami et al, 2001 ; Dang et al, 2008 ; Qiuhong et al, 2013 ; Benomar et al, 2015 ). However, the results are in conflict with others that demonstrated a positive latitudinal cline in A max driven by needle nitrogen ( N mass ) and carboxylation capacity ( V c max ) (Oleksyn et al, 1998 ; Soolanayakanahally et al, 2009 ).…”
Section: Discussionsupporting
confidence: 94%
“…For instance, leaf nitrogen concentration ( N mass ) and respiration rate ( R d ) have been found to increase with latitude and elevation while specific leaf area (SLA) decreases (Friend et al, 1989 ; Oleksyn et al, 1998 ; Hultine and Marshall, 2000 ; Qiuhong et al, 2013 ). Photosynthetic rate ( A max ) has also been reported to increase with latitude and elevation (Cordell et al, 1998 ; Oleksyn et al, 1998 ; Soolanayakanahally et al, 2009 ), but has been also reported to decrease or to have no linear relationships with latitude or elevation (Kogami et al, 2001 ; Dang et al, 2008 ; Qiuhong et al, 2013 ; Benomar et al, 2015 ). A max is affected by biochemical and biophysical processes and environmental conditions (Sharkey et al, 2007 ).…”
Section: Introductionmentioning
confidence: 99%
“…The seedlings were exposed to two CO 2 concentrations with (BGC-1) or without (BGC-0) belowground competitions at low (LN) and high (HN) nutrient supply for 4 months. Bars with different letters were significantly different from each other (P ≤ 0.05) the 223% enhancement reported by Dang et al (2008). The differences in the magnitude of enhancement might be attributable to variations in experimental protocols and genetic characteristics of the seedlings.…”
Section: Discussionmentioning
confidence: 69%
“…Therefore, it is possible that the small root volume in Johnsen's study has restricted seedling ability to take full advantage of the elevated CO 2 . Dang et al (2008) used seedlings from 11 provenances across Ontario while the current study used only one provenance. It is possible that the genetic potential of our provenance to respond to CO 2 elevation is lower than the average of the 11 provenances used in Dang et al (2008).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental manipulations in greenhouses (Dang et al, 2008) show that increased CO 2 fertilization from 360 mmol mol -1 (close to ambient atmospheric concentration) to 530 mmol mol -1 and 700 mmol mol -1 produced increased rates of water-use efficiencies for white spruce seedlings from a wide geographical range of provenances in Ontario, Canada (Fig. 5).…”
Section: Experimental Insights On Plant Responses To the New Arctic Cmentioning
confidence: 99%